High Blood Osmolality is Associated with Poor Neurological Status in Acute Ischemic Stroke Patient on Admission - Silalahi, Lothar Matheus Manson Vanende; Sutarni, Sri; Gofir, Abdul (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Purpose: The purpose of this study is to evaluate the association between high blood osmolality and neurological status in acute ischemic stroke. Methodology: This is a cross-sectional study. Subjects of this study are acute ischemic stroke patients admitted at Dr. Sardjito Hospital. Subjects who met the inclusion and exclusion criteria were analysed mainly the blood osmolality and NIHSS score at the time of admission. Results: The study involved 58 participants, with 29 (50%) exhibiting blood osmolality exceeding 300 mOsm/kg. A bivariate analysis revealed several factors significantly linked to poor neurological condition upon admission. These included elevated blood osmolality (OR=5,296, p=0,014, 95% CI, 1,29-21,7), presence of infection (OR=11,67, p=0,007, 95% CI, 1,95-6,99), increased white blood cell count (OR=4,750, p=0,028, 95% CI, 1,21-18,5), and an ASPECT Score below 7 (OR=14, p<0,001, 95%CI, 3,34-59). Multivariate analysis revealed that high blood osmolality (p=0,031) significantly associated with poor neurological status at the time of hospital admission. Applications: This study highlighted the importance of evaluating blood osmolality in acute ischemic stroke patients as it is associated with neurological deficit.